Simultaneous Non-Functioning Neuroendocrine Carcinoma of the Pancreas and Extra-Hepatic Cholangiocarcinoma. A Case of Early Diagnosis and Favorable Post-Surgical Outcome - Maurea, Simone; Corvino, Antonio; Imbriaco, Massimo; Avitabile, Giuseppe; Mainenti, Pierpaolo; Camera, Luigi; Galizia, Gennaro; Salvatore, Marco (JOP. Journal of the Pancreas, 2011)
Context Thanks to the wide use of diagnostic imaging modalities, multiple primary malignancies are being diagnosed more frequently and different associations of malignancies have been reported in this setting. Case report In this paper, we describe the case of a patient with non-functioning well-differentiated neuroendocrine carcinoma of the head of the pancreas associated with extra-hepatic cholangiocarcinoma, in which an early diagnosis using magnetic resonance imaging allowed a good outcome. Conclusion The simultaneous association of neuroendocrine pancreatic tumors and cholangiocarcinoma has not yet been described; however, this association should be considered and, due to the high contrast of magnetic resonance imaging, this technique is recommended in such patient in order to reach an accurate diagnosis. Image: T1-weighted fast-field echo short-time inversion recovery (FFE STIR) post-contrast image shows a solid lesion with inhomogeneous late-phase enhancement.